Delayed-Onset Continuous Bruxism with Olivary Hypertrophy After Top of the Basilar Syndrome - Kim, Seon-Gyung (Korean Neurological Association, 2006)
Delayed-onset continuous bruxism due to brain stem infarction has not yet been reported. A 49-year old man presented with quadriplegia and ophthalmoplegia. Brain MRI showed acute infarction in the bilateral midbrain, right thalamus and the superior cerebellum. One month later, the patient developed bruxism which persisted during sleep. A palatal myoclonus was not observed. Follow up MRI taken 4 months later showed bilateral olivary hypertrophy. We suggest that the patient's bruxism may be related to the olivary hypertrophy. The bruxism generator may be located in the pontine-reticular-formation (PRF). Bilateral large midbrain lesions interrupting the cortical inhibition may have produced bilateral olivary hypertrophy, which could stimulate the PRF, producing continuous bruxism.